The political economy of energy production in post-independence Tanzania: A review - Japhace Poncian; Rasmus Hundsbæk Pedersen (Danish Institute for International Studies (DIIS), 2023)
Energy is crucial to sustainable development globally. This working paper provides a critical review of the politics of energy production and how it manifests in supply and access in post-independence Tanzania. Drawing on existing scholarly analyses and grey literature, it paints a picture of some of the main political dynamics behind energy sector development in Tanzania. Energy production, transmission, supply, and access are contestable issues. The paper examines how energy politics have influenced government energy source choice and, more importantly, how renewable energy has featured in Tanzania's energy politics since independence and what this means for the broader agenda of renewable energy and sustainable development. Even though several rounds of policy reforms have placed emphasis on renewable energy, the scene has continued to be one dominated by hydro and non-renewable energy sources. Where non-hydro, renewable, energy projects have been built, these have only been mini-grid projects concentrated in rural areas. Large, non-hydro, renewable projects have not yet attracted adequate government interest. The regulatory and policy framework has not been in favour of large-scale, non-hydro renewables, even when the Government has appeared to commit itself to promoting them.
Keywords: 330; Tanzania; energy production; energy politics; neoliberal reforms; hydropower